O Advento de Deus e o êxodo humano: a A trindade na teologia da historia de Bruno Forte. - Silva, Pedro Igor Leite da (2020)
The present research intends to introduce the trinity thought by the Italian theologian Bruno Forte. To this end, it was necessary taking a pedagogical path that identified the theologian of history as a place where our object is thought. This way, before entering into the trinity relationship development, the research led us to a systematic study of the theoretical assumption which composes the comprehension of Forte’s history and its theologizing. And thanks to this epistemic retreat, two interconnected realities were able to be discovered: on one hand, this theology of history is the revelatio itself which, through the trinitarian paschal, allows a greater clarity regarded to the immanent mystery that advem to the economy. And, on the other hand, it enables a rereading of the creation, an interpretation of the present time and a hopeful anticipation of the eschatological fulfillment, humanity liberating destiny – always in the light of the Trinity. In this context, the God of the revelation is read as the Godwho-comes: He is the Advent, who goes down to the ranks of history to dialogue with the exodus condition of the human being, who is restless and constantly searching for some meaning. It is exactly by assuming to himself the cross of history, that God will seem interested to the man and that one, through his free decision, will correspond to that, assuming in the world the communion in several levels. The triune God assumes the history and the history, in an asymmetrical way, happens to be an icon of the impossible possibility to become the Beauty accessible to all. The methodology used was eminently bibliographical, which allowed a synchronic and diachronic reading of Forte’s text and, in part, of those who he keeps the dialogue: both in the theological field as in the mystical, art and philosophy field. This thesis, therefore, talks about the Trinity. However, we don’t talk about it from its depth, what would invalidate the research, but from the history (and its averse) in which the triune God was present, in order to it itself been understood in its totality.